Prostaglandins Pathway as a Possible Biological Link Between Cancer and Major Depression - Luca, Maria; Luca, Antonina; Celia, Agata; Calandra, Carmela (Current Angiogenesis (Discontinued), 2013)
Prostaglandins (PGs) are bioactive lipids involved in many physiological functions as well as in inflammation. The overexpression of PGs is a critical common point in the pathophysiology of cancer and depression: high plasmatic levels of these bioactive lipids have been reported in both disorders. In this review, the authors would like to deepen the role of PGs in cancer and depression, in order to make inquiries about a possible biological link (via the PGs pathway) between the two disorders, debating also over the implications of such a link in the therapeutic field.
Keywords: depression